P21 Predicting exacerbation frequency in patients with COPD using established risk factors. (11th November 2022) - Dobson, P; Dewar, A
Abstract : Introduction and Objectives: Exacerbations in COPD significantly affect quality of life and mortality. Predicting which patients are likely to exacerbate most frequently could provide opportunities to introduce treatment strategies to reduce future exacerbations. To determine whether established exacerbation risk factors can predict future exacerbation frequency and to assess the severity of an exacerbation risk factor on exacerbation outcomes. Methods: From the literature we identified risk factors associated with COPD exacerbations and categorised these into 'moderate' and 'severe'. We identified all patients who presented with a severe exacerbation of COPD to our unit from 01 January 2018 to 31 December 2018 and recorded their number of exacerbations over 18 months. Patients were divided into 8 groups based on exacerbation frequency. Standard statistical methods were applied. Results: A total of 213 patients were studied. Across all 8 patient groups there is a positive association between number of exacerbation risk factors and exacerbation frequency. The highest exacerbation frequency group has on average 5.0 severe risk factors compared to 2.3 severe risk factors for the lowest frequency group (p<0.001), and 2.7 moderate risk factors compared to 1.8 moderate risk factors for the lowest frequency group (p<0.05). Conclusions: The study demonstrates that it is possible to predict future exacerbation frequency amongst patients with COPD. Identifying which patients are at most risk of exacerbations may help clinicians to introduce pre-emptive individualised treatment strategies to reduce future exacerbation frequency.